1/3x=-2x+14

Simple and best practice solution for 1/3x=-2x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3x=-2x+14 equation:



1/3x=-2x+14
We move all terms to the left:
1/3x-(-2x+14)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
We get rid of parentheses
1/3x+2x-14=0
We multiply all the terms by the denominator
2x*3x-14*3x+1=0
Wy multiply elements
6x^2-42x+1=0
a = 6; b = -42; c = +1;
Δ = b2-4ac
Δ = -422-4·6·1
Δ = 1740
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1740}=\sqrt{4*435}=\sqrt{4}*\sqrt{435}=2\sqrt{435}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-42)-2\sqrt{435}}{2*6}=\frac{42-2\sqrt{435}}{12} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-42)+2\sqrt{435}}{2*6}=\frac{42+2\sqrt{435}}{12} $

See similar equations:

| G(x)=3+2 | | y-(-34)=25 | | 6/11=x/33 | | 3=k+11.5 | | 3(×—2)÷5(2—x)=16 | | y-(-35)=25 | | 1/3x=2x+14 | | 5d+2d-4=d+7-3d | | (X-10)+(2x-20)=90 | | (6x)^8/(6x)^14=0 | | 8h-20=4(2h-5) | | ((3x+1)/2)+((x-1)/3)=15/2 | | 3=—1(v-4)➕4(2v—9) | | 6.n+4=n-11 | | 2x0+-5=x | | ((1n)(1n))(2n)=16 | | 8x+4x+6x=180º | | 8(m+2)=4(2m+5) | | 3(3x-6)=7x-18+2x | | 12.77=2g+3.83 | | 2(3x+5)=5x+74 | | 5x/6-x/3=1 | | m^2-11m-136=-10 | | 5x-1/6=4x+1/3 | | (10-x)(6+x)=144 | | 2(-3x+1)=-2(x-4)-5x | | 4x-(2x-3)=13 | | 4x+12=40+2x | | 2/9(x)=-6 | | 2x^2-12x-113=-3 | | 9/x+4/2x=−3 | | 2/9z=-6 |

Equations solver categories